2013
DOI: 10.1016/j.jped.2013.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mass in Children and Adolescents Infected with Human Immunodeficiency Virus

Abstract: In the present sample children and adolescents living with HIV have low bone mass for age, and the use of protease inhibitors appears to be related to such decreases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 25 publications
1
22
2
2
Order By: Relevance
“…Post-pubertal HIV-infected males had lower adjusted WB BMC, as well as adjusted WB and LS BMD than controls. Another study conducted in Brazil found no sex differences in patterns of bone measures between HIV-infected boys and girls [61]. Determining whether the sex differences we observed persist throughout the period of skeletal maturation is an important area of future research.…”
Section: Discussionmentioning
confidence: 80%
“…Post-pubertal HIV-infected males had lower adjusted WB BMC, as well as adjusted WB and LS BMD than controls. Another study conducted in Brazil found no sex differences in patterns of bone measures between HIV-infected boys and girls [61]. Determining whether the sex differences we observed persist throughout the period of skeletal maturation is an important area of future research.…”
Section: Discussionmentioning
confidence: 80%
“…1420 In South Africa, school-aged children spend 20 minutes per day in moderate or vigorous physical activity. 913 However, no studies describe physical activity or sedentary behaviors among children with HIV who may have greater lifetime risk for cardiovascular disease due to cumulative lifetime exposure to HIV and ART.…”
mentioning
confidence: 99%
“…Incorporating the supplements into isoenergetic biscuits could also address the issue of blinding (if the non-LCP biscuits were dyed green) and might improve adherence and acceptability (28) . The Ca content of both supplements might be expected to ameliorate low bone mass, an effect of HIV infection that has been reported for children and adolescents (29) , although longer follow-up would probably be required to detect any such effects. Trials that aim to test novel dietary interventions would benefit from information obtained from qualitative research into local tastes and preferences (30) .…”
Section: Discussionmentioning
confidence: 93%